1999
DOI: 10.1046/j.1537-2995.1999.39199116892.x
|View full text |Cite
|
Sign up to set email alerts
|

NOR polyagglutination and Sta glycophorin in one family: relation of NOR polyagglutination to terminal α‐galactose residues and abnormal glycolipids

Abstract: Our results showed that two rare features of TS's RBCs, NOR polyagglutination and St(a) glycophorin, are inherited independently, and that NOR+ RBCs contain neutral glycolipids with an abnormal oligosaccharide structure, most likely terminated with alpha-galactosyl residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…Using a panel of lectins, the authors identified a new type of polyagglutination that was enhanced after treatment of NOR erythrocytes with proteases and was inhibited by sheep hydatic cyst fluid or avian P1 substance. Recently a second case of NOR polyagglutination has been identified in a two-generation Polish family (3). We found that polyagglutination of NOR erythrocytes, besides having the features described by Harris et al (2), was enhanced by sialidase and abolished by ␣-galactosidase treatment.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Using a panel of lectins, the authors identified a new type of polyagglutination that was enhanced after treatment of NOR erythrocytes with proteases and was inhibited by sheep hydatic cyst fluid or avian P1 substance. Recently a second case of NOR polyagglutination has been identified in a two-generation Polish family (3). We found that polyagglutination of NOR erythrocytes, besides having the features described by Harris et al (2), was enhanced by sialidase and abolished by ␣-galactosidase treatment.…”
supporting
confidence: 62%
“…Isolation of Glycosphingolipids-Neutral glycosphingolipids were isolated from lyophilized membranes of human NOR and control erythrocytes and rabbit erythrocytes as described previously (3). Briefly the procedure included two chloroform/methanol (2:1 and 1:2, v/v) extractions, treatment of the extracted and evaporated material with 0.2 M KOH in methanol to remove phospholipids, desalting the neutralized samples on the Sephadex G-25 superfine (Amersham Pharmacia Biotech) column, and separation of neutral glycolipids from gangliosides on the DEAE-Sephadex A-25 (Amersham Pharmacia Biotech) column.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar phenotype was then described in the Polish T.S. family (2). These two families are the only cases of NOR polyagglutination described so far.…”
supporting
confidence: 72%
“…Finally, washed cells were resuspended (5 ϫ 10 5 cells per 0.75 ml) and analyzed as described above. Extraction and Purification of Glycosphingolipids-The isolation and fractionation of glycolipids and the orcinol staining were performed using the standard procedures applied previously to erythrocytes (2,3). Briefly, glycolipids were extracted from 2102Ep cells with chloroform/methanol, and the neutral glycolipids were separated from the phospholipids and gangliosides, purified in peracetylated form, de-O-acetylated, and desalted.…”
Section: Methodsmentioning
confidence: 99%